Rychlost aortální pulzové vlny u nemocných s metabolickým syndromem a hypertenzí lécených sartany - Spác, J; Soucek, M; Rihácek, I; Nemcová, H; Pluhácek, L (Vnitrni lekarstvi, 2010)
INTRODUCTION: The incidence of subclinical organ damage is higher in patients with hypertension (HT) and metabolic syndrome (MS). Increased aortic pulse wave velocity (PWV) is one the markers reflecting subclinical arterial damage. Treatment with sartans leads not only to a reduction of blood pressure but may also bring regression of the subclinical damage. Long-acting sartans (telmisartan) may be more effective than sartans with medium duration of action (losartan); the aim of this research was to compare the impact of hypertension therapy with losartan and telmisartan on aortic pulse wave velocity (Ao-PWV). METHODS: We examined 32 patients with HT and MS, 15 patients were treated with losartan 50 mg (group A) and 17 patients were treated with telmisartan 80 mg (group B). At the beginning and the end of the study, PWV was measured using the Complior method and 24-hour BP monitoring and biochemistry testing were carried out. RESULTS: Treatment with sartans led to a reduction in BP in both groups, daytime BPs/BPd declined by 11.5/9.0 mm Hg in group A and by 13.8/8.1 mm Hg in group B, respectively, and night time BP declined by 5.7/5.1 mm Hg in group A compared to 7.4/3.89 mm Hg in group B. Aortal pulse wave velocity declined by 1.94 m/s in group A (p < 0.001) and by 0.46 m/s in group B (p < 0.001), respectively. CONCLUSION: Treatment with losartan as well as telmisartan resulted in reduced values of BP and Ao-PWV. We did not prove a more significant effect of a long-acting sartan (telmisartan) compared to a sartan with a medium duration of action (losartan) on Ao-PWV reduction after 1 year of treatment.
Keywords: hypertenze; Male; lidé středního věku; krevní tlak; Humans; Middle Aged; Metabolic Syndrome; mužské pohlaví; Female; Blood Pressure; ženské pohlaví; Angiotensin II Type 1 Receptor Blockers; Pulse; metabolický syndrom; aorta; Hypertension; lidé; Aorta; blokátory receptorů AT1 pro angiotensin II; pulz